PENGARUH PEMAHAMAN PERATURAN, ADMINISTRASI, DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK HOTEL DI KOTA DENPASAR - Pratiwi, Putu Surya; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
Tax compliance is the most important aspect in the taxation system in Indonesia by adopting self-assessment system that gives authority, trust, responsibility to the taxpayer to compute, calculate, pay and self-reported the amount of tax payable. In order to increase the level of tax compliance, to consider the factors that influence taxpayer compliance. The purpose of this study was to determine the effect of understanding the rules, the administration, and tax penalties on taxpayer compliance in the city of Denpasar. The samples used were 81 respondents to the proportionate method of sampling is stratified random sampling. Data was collected by questionnaire. The data analysis technique used is the technique of multiple linear regression analysis. The results obtained are understanding of regulatory, administrative and tax penalties and significant positive impact on taxpayer compliance hotel.
Keywords: tax compliance, understanding regulations, tax administration, tax penalties